Wzrost powierzchni naturalnego odnowienia świerka pospolitego (Picea abies L. Karst.) na Pojezierzu Kaszubskim w latach 2002–2012 - Szydlarski, Marcin; Modrzyński, Jerzy (Leśne Prace Badawcze, 2016)
The Kaszuby Lake District is located beyond the natural range of Norway spruce, however its share in local forest stands is considerable (14.8%) and its vitality and growth are here not less than within the natural range. The study presents the results of stock-taking of natural regeneration of Norway spruce in this region in year 2002 and 2012 and the relevant silvicultural recommendations. The stock of spruce natural regeneration was taken using the electronic database of the Regional Headquarters of State Forests in Gdańsk. The regeneration was put into following categories: seedlings (height below 0.5 m), lower advanced growth (height above 0.5 m and DBH below 7 cm), higher advanced growth (height above 3 m and DBH above 7 cm) and undergrowth (with dominating self sown spruce). In total 20 834 ha of Norway spruce natural regenerations were listed in year 2002 and 26 016 ha in year 2012 (increase by 24.9%). Most of them occur in fresh sites suited for mixed deciduous forests (LMśw) – in years 2002 and 2012 respectively 52.5% and 50.1%, and fresh sites suited for mixed coniferous forests (BMśw) – in years 2002 and 2012 respectively 30.4% and 32%. The increase of natural regeneration of Norway spruce in this period was connected with the 23.6% decrease in volume of spruce stands in age of above 40 years. Majority of spontaneously arriving spruce regenerations turn to the undergrowth, because of unfavorable light conditions under canopy and much to high density of seedlings and advanced growth. Good quality advanced growth on suited forest sites should be uncovered by thinning cuttings and consequently included into the future multispecies stands, with Norway spruce share up to 30%.